Characterization and Composition of Corrosion Scales in Drinking Water Distribution Systems - (:unkn) unknown (My University, 2022)
Internal corrosion of drinking water pipes has received considerable attention recently in the media and in academic studies due to compliance and monitoring regulations with the Lead and Copper Rule (LCR) established by the EPA in 1991. Notable health crises involving municipalities exceeding the LCR in Washington D.C. and Flint, Michigan occurred when corrosion scale conditions changed from stable to soluble lead compounds due to changing water chemistry, leaching high amounts of lead into consumers drinking water. Understanding the role of the corrosion scale in the process of leaching lead and other toxic trace metals such as arsenic is vital to ensure clean drinking water. Field-studies examining real-world corrosion scales in municipalities provide a glimpse into the effects of variable water chemistry conditions that can prove complimentary to bench-scale theory. In this study, three municipalities were chosen with different water quality, corrosion inhibitor, and disinfectant residual. The effect of water chemistry on corrosion scale formation within copper, iron, and lead pipes were important in the formation of corrosion scale minerals. Elemental analysis of the corrosion scales and their binding fractions were studied to derive the mechanisms of release so that water resource engineers can prevent this in the future.
Keywords: corrosion scales; drinking water corrosion; iron corrosion; lead corrosion; passivation; pipe corrosion